Medidas provisórias no contexto brasileiro: pressupostos constitucionais de relevância e urgência como condições de legitimidade democrática - Chaves, Bruna Salgado (2021)
The constitutional definition attributes to the provisional measures an exceptional character, guaranteed by the constitutional requirements of relevance and urgency. Its excessive use, as a technique of government, is susceptible to authoritarian tendencies and poses democratic risks due to the preponderance of the Executive Power in the formation of the normative order and exclusion from deliberative participation and, therefore, from popular sovereignty. Nevertheless, the synergy between the Executive and Legislative powers in converting these norms into law is insufficient to indicate the proactive and participatory posture of the Legislative Power in the control and processing of provisional measures issued by the Executive, deepened in the coalition presidential system. The research establishes the premisse of the deliberativ democracy as analysis criteria for the legitimacy and quality of democracy, upon which it investigates the role of the exception to the due legislativ process, in the use of provisional measures. The excepctionality of the instrument is persued through the analyzis of the definition of relevance and urgency in bibliographical and documental research, which refines the construction of its concepts through doctrinal and jurisprudential contributions. From this, a harmonious institutional relationship for the edition of provisional measures is analyzed in the context and limitations of coalition presidentialism. The finding of the excessive use of provisional measures is demonstrated by their normative impact, when compared to the number of ordinary laws published in the same period. It also analyzes the meaning of the assumptions of demand and urgency by the Executive and Legislative Powers in 308 provisional measures, in order to identify the criteria of their significance through institutional dialogues. When confronted with the democratic premises and the will of the Federal Constitution of 1988, it appears that the coordinated action between the Executive and Legislative powers for the excessive use of provisional measures does not maintain democratic legitimacy and supplants constitutional coerciveness due to the exceptional character of the institute, maintaining the risks of the preponderance of the Executive Power in the formation of the normative order, with a tendency towards civil authoritarianism.